ANALISIS SEMOTIKA LAGU MANGU DARI FOURTWNTY DALAM INTEPRETASI PERCINTAAN BEDA AGAMA - Adi Aminudien, Fakhri; Dewi Nuraini, Lisna (Institut Nahdlatul Ulama Tasikmalaya, 2025)
Songs or music are one form of musical communication because they contain meaning with symbols contained in the lyrics. This study aims to reveal the hidden meaning of the song